A general approach on collision-free workspace determination via triangle-to-triangle intersection test. (April 2017) - Danaei, Behzad; Karbasizadeh, Nima; Tale Masouleh, Mehdi
Abstract: This paper introduces a new general systematic approach using the so-called triangle-to-triangle intersection test in order to obtain the collision-free workspace of robotic mechanical systems. In this geometric constructive approach, a collision test will be performed, based on the STL file, for all possible configurations of the robot which leads to obtain the collision-free workspace. By introducing a bounding sphere, the obtained results from the proposed algorithm reveal that the computational time on average is 0.0490 μ s per test which is reduced by 23% comparing to one of the recent algorithm proposed in the literature. Furthermore, the collision-free workspace determination approach provides a statistical data about the percentage of collision for each constituting part of the mechanism. By resorting to the latter statistical data, an index for collision-free workspace is introduced which provides some insights into designing a well-conditioned workspace in terms of mechanical interference. The approach is implemented on two cases studies, namely 3-RRR and the so-called Tripteron parallel mechanisms. Abstract : Highlights: A fast and improved approach for triangle-to-triangle intersection test is proposed. A general approach for obtaining the collision-free workspace—by considering mechanical interference, joint limits and obstacle—is proposed. An index is introduced which indicates the efficiency of the robots with respect to the workspace area (volume). The proposed approach provides insight into designing a well-conditioned workspace with respect to mechanical interference. Two case studies, namely, 3-RRR and Tripteron parallel mechanisms, are treated for which some insights are given for their optimal design and performance.